From Experiment to Innovation: The Effect of Experiential Learning on Elementary School Children’s Science and Critical Thinking Skills - Silvia Erawati; Woro Sri Hastuti (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2025)
The implementation of learning with conventional models does not provide direct experience which results in minimal opportunities for students to explore, reflect, and present scientific findings, especially in elementary schools. This study aims to analyze the effect of the implementation of the Experiential Learning model on science process skills in communicating, critical thinking skills, and its comparison with the Problem Based Learning model in grade IV elementary school students. The type of quasi-experimental research with a nonequivalent control group design, with a sample of grade IV elementary school students taken by purposive sampling. The instruments, in the form of essay tests, were declared valid and reliable with a Sig. (2-tailed) value of 0.000 and Cronbach's Alpha of 0.661 for science process skills and 0.728 for critical thinking skills. Data were analyzed using independent sample t-test and MANOVA with a significance level of 0.05. The results showed that the Experiential Learning model had a significant effect on both science process skills in communication and critical thinking skills, with a significance value of 0.000. MANOVA testing also indicated a significant effect of the model on both variables, with partial eta squared values of 67.5% for science process skills in communication and 30% for critical thinking skills. This indicates that the Experiential Learning model is effective in enhancing both abilities among fourth-grade elementary school students.